(untitled) (Modern information system and technologies, 2018)
The article discusses the concept of "web analytics", as well as examines the basic methods and tools for effective web statistics. Web analytics allows you to collect and analyze data about visitors and, on the basis of them, develop a system of actions and measures for the effective development of a web resource. Keywords: web analytics, usability, benchmarking, behavioral factors, conversion.